Effect of yacon (Smallanthus sossnchifolius) tuber extract addition on chemical and organoleptic characteristics of green tea kombucha - Nabilah Hening Prayitno; Irma Sarita Rahmawati; Fajar Ari Nugroho (AcTion: Aceh Nutrition Journal, 2026)
Kombucha is a fermented beverage produced from tea, sugar, and a symbiotic culture of microorganisms. Yakon tubers have a natural sweetness and contain phenolic compounds, fructooligosaccharides, and inulin, which function as natural prebiotics. However, studies on the incorporation of yakon tubers into green tea kombucha are limited. This study aimed to evaluate the effect of yakon tuber extract on the chemical and organoleptic characteristics of green tea kombucha. A true experimental design with a Completely Randomized Design was applied using four formulations: F0 (0%), F1 (10%), F2 (20%), and F3 (30%). The parameters analyzed included pH, total sugar content (DNS method), total flavonoid content (UV–Vis spectrophotometry), and sensory evaluation by 30 panelists, carried out for 1 month at Universitas Brawijaya. Data were analyzed using one-way ANOVA/Kruskal–Wallis/Mann–Whitney and Duncan’s Multiple Range Test (DMRT), as appropriate. The results showed that the addition of yakon extract reduced the total sugar content (p=0.015) and increased the total flavonoid content (p=0.000). The final pH values were within a safe range (2.54–2.62), with no significant differences in the sensory attributes (p>0.05). Yakon tubers support microbial growth during fermentation. Formulation F3 (30%) was identified as the best treatment based on its acceptable pH, lower sugar content after dilution, and highest panelist preference.